2020
DOI: 10.22271/chemi.2020.v8.i1l.8370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic, inorganic and integrated nutrient management on yield attributes, production of onion and soil properties, under vertisol of Maharashtra

Abstract: Field experiment was conducted in rabbi season of 2016-17 at Research Farm of at AICRP on Integrated farming System. Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani entited "Effect of Organic, Inorganic and Integrated Nutrient Management on Soil Properties, Production and Economics of Onion Under Vertisol". The experiment was laid out on Vertisols with eight treatment combination, replicated three times in randomized block design. Application 50% recommended NPK +50% N trough FYM/crop residues/compost/ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…A gradual increase in nitrogen, phosphorous and potassium content of leaves was observed with increasing levels of nitrogen and phosphorous fertilizers in all growth stages of yam bean crop. These results are in close conformity with results reported by Salvi et al, (2014) [30] and Rathod et al, (2018) [26][27][28] who reported significantly highest nitrogen, phosphorous and potassium content due to integration of inorganic fertilizers, poultry manure and Azotobacter. The treatment receiving 120:80:100 N , P 2 O 5 , K 2 O kg ha -1 + 20t FYM ha -1 noted significantly highest levels of nutrients in leaves at all growth stages.…”
Section: Results and Discussion Nutrient Content Of Yam Bean Leavessupporting
confidence: 92%
See 2 more Smart Citations
“…A gradual increase in nitrogen, phosphorous and potassium content of leaves was observed with increasing levels of nitrogen and phosphorous fertilizers in all growth stages of yam bean crop. These results are in close conformity with results reported by Salvi et al, (2014) [30] and Rathod et al, (2018) [26][27][28] who reported significantly highest nitrogen, phosphorous and potassium content due to integration of inorganic fertilizers, poultry manure and Azotobacter. The treatment receiving 120:80:100 N , P 2 O 5 , K 2 O kg ha -1 + 20t FYM ha -1 noted significantly highest levels of nutrients in leaves at all growth stages.…”
Section: Results and Discussion Nutrient Content Of Yam Bean Leavessupporting
confidence: 92%
“…It was medium in available nitrogen (420.57 kg ha -1 ), very low in available phosphorous (11.74 kg ha -1 ) and high in available potassium (297.38 kg ha -1 ) content in its initial physio-chemical analysis. These Results are in line with the results reported by Shinde et al, (2010) [33] , Salvi et al,(2014) [30] and [26][27][28] . In general, it can be concluded that soil of experimental site indicated typical lateritic soil of Konkan region.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…The increased bulb formation, larger-sized onions, and overall improved yield might be since organic manure supplied balanced nutrition to the crop, improved soil condition and thereby resulted in better growth and development leading to higher yield. The above outcomes are correspondingly in nearby conformism by the result of Thangasamy et al [6], Sharma et al [7] Rathod et al [8] and Verma et al [9] in Allium cepa L.…”
Section: Effect Of Integrated Nutrient Management On Yield Of Onionmentioning
confidence: 72%
“…Recent research has shown that dietary onions can help prevent heatstroke and other disorders [13]. The onion bulb [14] is abundant in carbohydrates, calcium, and phosphorus.…”
Section: Introductionmentioning
confidence: 99%